Analisis Yuridis pada Putusan Pengadilan Negeri Sangeti Nomor 71/Pid.B/LH/2021/PN Snt dalam Perspektif Hukum Pembangunan Berkelanjutan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Sustainable development always requires harmony between economic, environmental and social aspects in its planning. In Indonesia, the provisions of sustainable development are regulated in laws and regulations so that the law can be used as a means to implement the concept of sustainable development so that the harmony between the aspects of sustainable development can be carried out properly. This research aims to analyze the implementation of the concept of sustainable development in Decision No. 71/Pid.B/LH/2021/PN Snt. This research uses a normative legal approach with descriptive analytical research. The legal materials used are primary legal materials. The results show that law enforcement, in this case sustainable development law, should not only consider environmental aspects, but should also consider other aspects such as economic and social aspects.